2012
DOI: 10.2131/jts.37.23
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL and Mcl-1 are involved in prevention of in vitro apoptosis in rat late-stage erythroblasts derived from bone marrow

Abstract: -Apoptosis controls erythroid homeostasis by balancing survival and death of erythroid cells. The mitochondrial pathway of apoptosis involves regulation of apoptotic events caused by the Bcl-2 family proteins, including the anti-apoptotic and pro-apoptotic members. However, little has been reported on the role of the anti-apoptotic Bcl-2 family members in rat late-stage erythroblasts that are no longer erythropoietin (EPO)-dependent. In the present study, to investigate this we analyzed changes in apoptosis-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, anti-apoptotic Bcl2l1/Bcl-xL, Mcl1, Trib3 and pro-apoptotic Nix (coexpressed with Bcl-xL during erythroid maturation) were not upregulated in KIT D816V cells (Figures 4a and b, Supplementary Figure 4A). 21,[37][38][39][40] Alongside, downregulation of Bad and Bid was impaired (Figure 4a). These data show that continuous Kit signaling perturbs induction of the transcriptional program associated with terminal erythroid maturation and interferes with regulation of key mediators of cell cycle control, cell death and survival, thereby leading to continued proliferation and elevated apoptosis during terminal differentiation.…”
Section: Kitmentioning
confidence: 98%
“…Moreover, anti-apoptotic Bcl2l1/Bcl-xL, Mcl1, Trib3 and pro-apoptotic Nix (coexpressed with Bcl-xL during erythroid maturation) were not upregulated in KIT D816V cells (Figures 4a and b, Supplementary Figure 4A). 21,[37][38][39][40] Alongside, downregulation of Bad and Bid was impaired (Figure 4a). These data show that continuous Kit signaling perturbs induction of the transcriptional program associated with terminal erythroid maturation and interferes with regulation of key mediators of cell cycle control, cell death and survival, thereby leading to continued proliferation and elevated apoptosis during terminal differentiation.…”
Section: Kitmentioning
confidence: 98%
“…Mcl-1 expression, just like Bcl-xL expression, is highly induced under conditions that are conducive to survival and by differentiation signals from cytokines and growth factors [11,12]. Mitogen-activated protein kinase (MAPK)-phosphatidylinositol-3 (PI3K)- and Janus kinase (JAK)/signal transducer and activator of transcription (STAT)-dependent pathways have all been implicated in the stimulation of Mcl-1 transcription, acting via specific transcription factor response elements in the Mcl-1 gene promoter [13-15].…”
Section: Introductionmentioning
confidence: 99%
“…EPO/EPOR binding upregulates Bcl-xl expression via inhibition of caspase activities, thus resulting in the protection of erythroid cells from apoptosis [ 33 , 34 ]. A rat study showed that EPO stimulation resulted in reduced apoptotic cells death of late-stage erythroblast accompanied by decreased caspase-3 and caspase-9 activities and upregulated the Bcl-xl mRNA, resulting in decreases in the mRNA ratios of Bak, Bax, Bad, to Bcl-xl, which is indicative of the induction of apoptosis through mitochondrial pathway in rat late-stage cultured erythroblasts derived from bone marrow [ 35 ] and Bcl-xl and Mcl expression increase and Bid, Bax, and Bim decrease in bone marrow-derived definitive erythroblasts [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%